2018
DOI: 10.1021/acssuschemeng.7b04535
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Microwave-Assisted Lignin Solubilization in Protic Ionic Liquids with Multiaromatic Imidazolium Cations

Abstract: The low solubility of lignin in most common solvents remains a significant challenge to be solved for its use and recovery. In this work, 18 novel protic ionic liquids (ILs) containing aromatic-substituted imidazolium cations and methanesulfonate and p-toluenesulfonate anions were synthesized and evaluated for lignin dissolution under microwave irradiation. ILs containing methanesulfonate demonstrated good lignin dissolving capacities, which can facilitate its separation and structural modifications to carry o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 48 publications
2
13
0
Order By: Relevance
“…THEAL demonstrated to be an excellent solvent for lignin reaching a maximum of 47.09 wt % lignin solubility at 353.15 K (Figure ). This is a noteworthy value achieved with a lower temperature than that reported in similar studies using other solvents. ,,, …”
Section: Resultssupporting
confidence: 44%
See 3 more Smart Citations
“…THEAL demonstrated to be an excellent solvent for lignin reaching a maximum of 47.09 wt % lignin solubility at 353.15 K (Figure ). This is a noteworthy value achieved with a lower temperature than that reported in similar studies using other solvents. ,,, …”
Section: Resultssupporting
confidence: 44%
“…39−45 Recently, PILs have been proposed for lignin dissolution. 20,28 The ability of 18 novel multiaromatic PILs for Kraft lignin dissolution was visually demonstrated by Merino et al using microwave-assisted irradiation at 363.15 K. The results The authors also reported, in general, a negative effect of water on lignin solubility; however, a hydrotropic behavior was observed for 2-hydroxyethylammonium octanoate (HEAO) that enhanced lignin solubility in aqueous solutions to a maximum value at 40 wt % water content. 46,47 A wide range of cation and anion combinations could be used to synthesize PILs, but only a few of these possibilities are reported in the literature for lignin dissolution.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…Several studies have presented that different solvents like ethylene glycol, DMSO [80], ILs [81], g-valerolactone [34] and Tween-80/H 2 O are able to dissolve up to 70 wt% lignin [82]. Among these solvents, ILs have acquired especial levels of interest due to their particular chemo-physical properties when compared to traditional molecular solvents.…”
Section: Lignin Separation With Ilsmentioning
confidence: 99%